If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1(3x + -10) = 46 Reorder the terms: 1(-10 + 3x) = 46 (-10 * 1 + 3x * 1) = 46 (-10 + 3x) = 46 Solving -10 + 3x = 46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 3x = 46 + 10 Combine like terms: -10 + 10 = 0 0 + 3x = 46 + 10 3x = 46 + 10 Combine like terms: 46 + 10 = 56 3x = 56 Divide each side by '3'. x = 18.66666667 Simplifying x = 18.66666667
| 12x-25=-63+7x | | 3(-2x+5)=12-4x | | -8x+4=-2(4x-2) | | -y=12-6x | | -20=2y-4 | | monkey+hat=toad | | 6x-y=12fory | | 8x+4=-2(4x-2) | | G=(x+y)(ax+bxy) | | ln(4-x)+ln(2)=2ln(x) | | G=ax(x+y)+bxy(x+y) | | 5w+10=5w+10 | | -19x-34=56+x | | 25-5x=4x-20 | | 16x-19=120+6x | | 10x+8x+12x+4x+9x+3-12-9+2-3=360 | | 3x+4=9+x | | 2x+9=3x-20 | | 11x+16=3x+13 | | 3(x+12)=9x-14 | | 4(3x-1)=8(x+9) | | 2(x+20)=7x+150 | | -0.333b=9 | | x=5andx-5 | | 5x=-15+5y | | 5(1-7r)=25 | | 23=2+7(z+6) | | x=70-2.5y | | X+2+x+x+x=6-x | | 2+2=goldfish | | an=5+0.2(n-1) | | 4x-6x-3=x+6 |